The Pitfalls of the Bell Curve in Performance Management - Michael Mncedisi Willie (Yayasan Aya Sophia Indonesia, 2025)
This conceptual paper critically examines the continued application of the bell curve model in performance management systems, highlighting its limitations and proposing alternatives better aligned with contemporary organisational needs. While the bell curve, or forced distribution model, aims to standardise employee evaluations by assuming performance follows a normal distribution, it often misrepresents actual contributions, particularly in high-performing teams, knowledge-based sectors, and dynamic environments. Drawing on systems theory and equity theory, this study argues that the model neglects contextual, collaborative, and developmental dimensions of performance, reinforcing biases and undermining fairness and engagement. A thematic review of scholarly literature and case studies from 2020 to 2024 reveals recurring criticisms, including the distortion of team dynamics, misalignment with job complexity, and erosion of employee morale. The analysis supports a shift toward more adaptive, inclusive, and feedback-oriented appraisal systems that emphasise growth, equity, and contextual relevance. The paper advocates for abandoning rigid ranking systems and favouring developmental models that recognise diverse contributions and foster sustainable performance cultures.